Pelatihan Peningkatan Computational Thingking Guru sebagai Persiapan Menghadapi Era Pembelajaran Coding Pada Pembelajaran PAUD - Ismiatun, Asih Nur; Siregar, Masyunita; Amanda, Rizki Surya; Hasni, Uswatul; Rosyadi, Akhmad Fikri; Kasmiati, Kasmiati (Perkumpulan Manajer Pendidikan Islam Indonesia (PERMAPENDIS) Prov. Sumatera Utara, 2025)
Computational thinking is becoming one of the most important skills in the 21st century. Computational thinking skills are not only about computer science but also about problem-solving skills, so they should be trained and mastered by every individual. Computational thinking has become a popular skill in education, where educators are also required to possess this skill as an indicator of teachers who are able to adapt to the era of educational reform and prepare a generation to face future challenges. This ability can be measured through aspects of abstraction, decomposition, algorithms, evaluation, and generalization. This training involved kindergarten teachers in Kerinci Regency, with the aim of improving computational thinking skills for the era of coding learning in early childhood education (PAUD).